Distributional effects of reducing energy subsidies: Evidence from recent policy reform in Argentina - Fernando Giuliano; Maria Ana Lugo; Ariel Masut; Jorge Puig (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2020)
We analyze the distributional effects of the reduction in energy subsidies in Argentina since 2016. As the policy reform also includes the introduction of a scheme to protect less well-off families (social tariff), we also review how well the targeting mechanism works. We apply traditional benefit-incidence analysis using household surveys and administrative data, focusing on residential subsidies to natural gas and electricity in the Buenos Aires Metropolitan Area. We find that the social tariff is relatively pro-poor, with significantly higher coverage among the poorest households. There are some exclusion errors in the low-income deciles and large inclusion errors in the medium- and high-income deciles. The distributive incidence of subsidies does not appear to have changed substantially. Energy subsidies in Argentina (lower in aggregate terms) continue to be, although progressive, pro-rich. The distributional effect is explained by the fact that generalized subsidies to all categories of consumption coexist with a relatively well targeted social tariff. Regarding energy budget shares, monthly spending on electricity has increased from 1.1 percent of total household income to 3.4 percent. Monthly spending on piped gas rose from 1.3 percent to 3.3 percent. These shares are in line with many other countries in the region. Naturally, there has been a convergence of tariffs toward service provision costs.
Keywords: H22; D31; D78; Q48; 330; distributive incidence; subsidies; energy; policy reform